Mechanically induced phase transformation of zinc sulfide - Damm, Cornelia; Armstrong, Patrick; Roßkopf, Christian; Romeis, Stefan; Peukert, Wolfgang (Particuology, 2015)
Molecular dynamics (MD) simulations of the consecutive compression-decompression cycles of hexagonal zinc sulfide (wurtzite) nanoparticles predict an irreversible phase transformation to the cubic polymorph. The phase transformation commences at the contact area between the particle and the indenter and proceeds with the number of compression cycles. Dislocations are visible for a particle size above 5 nm. Results from wet grinding and dry powder compression experiments on a commercial wurtzite pigment agree qualitatively with MD simulation predictions. X-ray diffraction patterns reveal that the amount of cubic polymorph in the compressed samples increases with pressure applied to the powder. In comparison with powder compression, wet milling leads to a more pronounced phase transformation. This occurs because the particles are exposed to a large number of stress events by collision with the grinding media, which leads to the formation of defects and new surface crystallites by particle fracture. According to the MD simulations, phase transformation is expected to occur preferentially in surface crystallites because they experience the highest mechanical load. Because of the phase transformation, the wet ground and compressed samples exhibit a lower photoluminescence intensity than the feed material. In comparison with powder compression, milling reduces the photoluminescence intensity more substantially. This occurs because a higher defect concentration is formed. The defects contribute to the phase transformation and photoluminescence quenching.
Keywords: Molecular dynamics simulation; Polymorph transformation; Powder compression; Wet milling; Zinc sulfide

Microstructural evolution during deformation of tin dioxide nanoparticles in a comminution process - Armstrong, Patrick; Knieke, Catharina; Mackovic, Mirza; Frank, Gerhard; Hartmaier, Alexander; Göken, Mathias; Peukert, Wolfgang; Mackovic, Mirza (Acta Materialia, 2009)
Nanoparticles can be produced by wet grinding in stirred media mills if agglomeration is prevented by stabilization of the particles. Since the fracture mechanisms at the lower nanoscale are not yet understood, we studied the evolution of the microstructure within tin dioxide particles. Electrostatic stabilization allows the formation of tin dioxide with a mean particle size of 25 nm as measured by dynamic light scattering. High-resolution transmission electron microscopy (HRTEM) images show particles well below 10 nm and mean crystallite sizes of 9 nm were obtained from X-ray diffraction by applying the Rietveld refinement method. Additionally, TEM and HRTEM analyses were conducted to gain detailed insight into the microstructural effects governing the grinding process. Microscopy revealed surprisingly rich phenomena including the formation of shear bands, twinning and stacking faults that directly affect the grinding behavior. Interestingly the ceramic nanoparticles showed not only fracture patterns expected from brittle fracture but also many traces of plastic deformation. For comparison the uniaxial compression of particles up to 30 nm in diameter was simulated using molecular dynamics. The simulated particles shared microstructural details with the real samples, most importantly the shear bands which lead to significant plastic deformation. The internal microstructure produced during multiple particle stressing events in the mill and also observed in the simulations is directly linked to the fracture mechanism and the experimentally observed grinding limit. © 2009 Acta Materialia In
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.micros
Keywords: Molecular dynamics simulations; Nanomechanics; Nanostructure; Shear bands; Transmission electron microscopy (TEM)

Minkowski Tensor Shape Analysis of Cellular, Granular and Porous Structures - Peukert, Wolfgang; Schröder-Turk, Gerd; Mickel, Walter; Kapfer, Sebastian; Klatt, Michael; Schaller, Fabian; Hoffmann, Matthias; Kleppmann, Nicola; Inayat, Amer; Armstrong, Patrick; Hug, Daniel; Reichelsdorfer, Martin; et al. (Advanced Materials, 2011)
Predicting physical properties of materials with spatially complex structures is one of the most challenging problems in material science. One key to a better understanding of such materials is the geometric characterization of their spatial structure. Minkowski tensors are tensorial shape indices that allow quantitative characterization of the anisotropy of complex materials and are particularly well suited for developing structure-property relationships for tensor-valued or orientation-dependent physical properties. They are fundamental shape indices, in some sense being the simplest generalization of the concepts of volume, surface and integral curvatures to tensor-valued quantities. Minkowski tensors are based on a solid mathematical foundation provided by integral and stochastic geometry, and are endowed with strong robustness and completeness theorems. The versatile definition of Minkowski tensors applies widely to different types of morphologies, including ordered and disordered structures. Fast linear-time algorithms are available for their computation. This article provides a practical overview of the different uses of Minkowski tensors to extract quantitative physically-relevant spatial structure information from experimental and simulated data, both in 2D and 3D. Applications are presented that quantify (a) alignment of co-polymer films by an electric field imaged by surface force microscopy; (b) local cell anisotropy of spherical bead pack models for granular matter and of closed-cell liquid foam models; (c) surface orientation in open-cell solid foams studied by X-ray tomography; and (d) defect densities and locations in molecular dynamics simulations of crystalline coppe
Keywords: geometric; statistic; spatial; anisotropy; shape; morphology; crystal

Size effects in the elastic deformation behavior of metallic nanoparticles - Armstrong, Patrick; Peukert, Wolfgang (Journal of Nanoparticle Research, 2012)
In this work, the results of a series of molecular statics simulations to investigate the size dependence of the elastic properties of metallic nanoparticles are presented. The per-atom stiffness tensor was calculated from the derivative of the used embedded atom method potentials and, from it, lower order elastic parameters, such as the Young's modulus or the Poisson ratio. The Young's modulus decayed up to 30 % relative to the bulk values for 2.5 nm small particles, whereas the Poisson ratio showed an increase with decreasing particle size for most materials. Particles with a diameter of 30 nm approached the continuum values to around 1 %, marking the transition to continuum theory. The size-dependent Young's modulus and several other material properties can be described by a simple algebraic function of the number of atoms per particle. By plotting the radial distribution of the local Young's modulus within particles of different size, it is shown that only the outermost 2-3 atomic layers are responsible for the size-dependent change of elastic properties. Within these layers, the average atomic stiffness was found to decay linearly and independent of the particle siz
Keywords: Size effect; Elasticity; Molecular statics; Nanoparticles; Young's modulus